The Gender Gap: Past, Present and Perspectives - Frank ELBERS; Ana-Maria GRIGORE (Revista de Management Comparat International)
Nowadays in most industrialised countries women outperform men at all education levels but in the workplace they are under-paid and under-promoted. At the same time there is broad global consensus that gender equality is a fundamental human right and, in fact, is linked to a country’s overall economic performance. Although in Romania the status of women has improved considerably in recent years, differences between women and men in economic participation still persist. The aim of this paper is to answer the question: where do we stand today with regard to the gender gap in the economy? The research is based on official reports on gender inequality, data collected by the European Union, United Nations and World Economic Forum, legislation in force, and the most important and relevant studies in the literature, which all point to a continued gender gap in Romanian society.